Microencapsulated nanostructured lipid carriers as delivery system for rutin. (16th April 2018) - Gan, Liang; Zhang, Chen; Wu, Fengjuan; Li, Hong; Zhang, WanPing; Zhang, Qianjie
Abstract: A new delivery system based on loading of drug into nanostructured lipid carriers (NLC) and then encapsulating it into hydroxypropyl-β-cyclodextrin (HPCD) has been developed for rutin (RT) to overcome its limitation for practical application. Light microscope, scanning electronic microscope (SEM) and differential scanning calorimeter (DSC) were used to determine the morphology, microstructure and thermal properties of rutin-loaded microencapsulated nanostructured lipid carriers (RT-loaded MNLC), respectively. The effect of HPCD on the performance of RT-loaded MNLC was investigated in terms of particle size, entrapment efficiency, UV absorptivity and in vitro release. It is revealed that the combined encapsulated technology could successfully resolve the leakage and instability problems of rutin. The obtained RT-loaded MNLC in the size range of 210–270 nm (polydispersity index < 0·4) were spherical and homogeneous. The presence of HPCD influences the particle size, entrapment efficiency and release profile of rutin and has synergistic effect on UV protection.